El Dionisos de Nietzsche en América Latina (1900-1925) - Cortez, David (2018)
“Nietzsche’s Dionysus in Latin America (1900-1925)”. This essay analyzes some of Nietzsche’s readings and, in particular, his representation of Dionysus, which some Latina American lettered elites elaborated in the first quarter of the twentieth century in their quest to legitimize themselves before the expansion of positivist and utilitarian projects that caused a cultural and political deficit in Latin American societies. It is argued, on the one hand, that the recourse to the Dionysius of Nietzsche energized a modernizing movement in the context of modernized societies in the processes of secularization and, on the other hand, that the critical perspective gained by recourse to the Dionysus of Nietzsche did not escape the reproduction of colonial and neocolonial narratives from discourses on “what is ours”, “latino,” “hispanic,” “catholic”, among other formulations.